Human immunodeficiency virus type 1 mutants that escape neutralization by human monoclonal antibody IgG1b12. off. - Mo, H (1997)
IgG1b12, a human monoclonal antibody (MAb) to an epitope overlapping the CD4-binding site on gp120, has broad and potent neutralizing activity against most primary human immunodeficiency virus type 1 (HIV-1) isolates. To assess whether and how escape mutants resistant to IgG1b12 can be generated, we cultured primary HIV-1 strain JRCSF in its presence. An escape mutant emerged which was approximately 100-fold more resistant to neutralization by IgG1b12. Both virion-associated and solubilized gp120 from this variant had a reduced affinity for IgG1b12, and sequencing of its env gene showed that amino acid substitutions had occurred at three positions within gp120. Two (D164N and D182N) were located in V2, and one (P365L) was in C3. By site-directed mutagenesis, we demonstrated that the D182N and P365L mutations, but not D164N, contribute to the IgG1b12-resistant phenotype. However, the former two substitutions, individually or in combination, hinder the replication of the neutralization-resistant virus. Introduction of the D164N substitution into the P365L variant results in a nonviable virus (D164N/P365L). In contrast, addition of D164N to the D182N or D182N/P365L mutant partially restored replicative function to near wild-type levels. Furthermore, we found that all of the IgG1b12-resistant mutant viruses remained sensitive to other human MAbs, such as 2G12 and 2F5, and to the CD4-IgG molecule, except that the P365L-containing mutant was slightly resistant to CD4-IgG. These results suggest that escape from IgG1b12 neutralization is due to a local rather than a global modification of the gp120 structure. Our findings have implications for the therapeutic and prophylactic applications of antibodies for HIV-1 infection.